Intrecci. Esperienze di ricerca, didattica e terza missione in ambito antropologico - Porcellana, Valentina (Antropologia Pubblica, 2024)
Through two action-research that have been developed over the past two decades, the article traces the evolution of the notion of third mission and its application within Academic institutions in Italy. A participatory research method has matured over time, involving researchers, students and citizens in both urban and geographically marginalized contexts, with the aim of introducing new practices of inclusion. Through the analysis of these experiences, the constraints and possibilities of applied and public anthropology emerge, related to the multiplication of variables and actors involved in carrying out field research, the difficulty of obtaining funding from entities outside the university, and the critical issues related to the evaluation of complex processes that must be monitored in itinere.